Clinical assessment of balance and functional impairments in people with stable chronic obstructive pulmonary disease: a systematic review and meta-analysis - Rodrigo Núñez-Cortés; Paloma Padilla-Acevedo; Franchesca Vergara-Peña; Sara Mollà-Casanova; Claudia Espinoza-Bravo; Rodrigo Torres-Castro; Carlos Cruz-Montecinos (ERJ Open Research, 2022)
The objective of this study was to compare the balance and functional capacity between stable chronic obstructive pulmonary disease (COPD) patients versus healthy controls using clinical tests. A comprehensive search of PubMed/MEDLINE, the Cochrane Central Register of Controlled Trials (CENTRAL), Embase and Web of Science was conducted from inception to 21 January 2022. Studies reporting the association between COPD status and balance or functional capacity using clinical tests were included. Two independent reviewers examined the titles and abstracts, extracted the data using a standardised form, and assessed the risk of bias of the included articles. A total of 27 studies with 2420 individuals with stable COPD were included. Overall, the risk of bias in the included studies was low to moderate. The meta-analysis showed a higher history of falls in individuals with COPD (odds ratio 1.59, 95% CI 1.25–2.02). Furthermore, an overall effect in favour of the healthy controls was observed in the Timed Up and Go (mean difference: 2.61 s, 95% CI 1.79–3.43), Berg Balance Scale (mean difference: −6.57 points, 95% CI −8.31 to −4.83), static balance tests (standardised mean difference: −1.36, 95% CI −2.10 to −0.62) and the 6-min walk test (mean difference: −148.21 m, 95% CI −219.37 to −77.39). In conclusion, individuals with stable COPD have worse balance and functional capacity compared to healthy controls. These results may guide clinicians to elaborate on therapeutic strategies focused on screening of balance and functional impairments. This is in addition to generating rehabilitation guidelines aimed at reducing the risk of falling in people with COPD.